دور لاثقافة التنظيمية في تكريس حوكمة قطاع التعليم العالي دراسة ميدانية على مستوى كلية العلوم الاقتصادية جامعة محمد بوضياف - أمغار امينة (جامعة المسيلة, 2024)
: 􀊝􀊳 ل􀊸 ال ة 􀊺􀘗􀊨 ح 􀈏 اد 􀥼 م 􀊝􀈄􀊛􀘔 قلا، في ت 􀊱􀊶 م 􀊛ا 􀊽 غ􀊱 صفها م 􀊨 ة ب 􀥽􀊺􀥽􀊤􀊻􀊱 قافة ال 􀊲 فة دور ال 􀊛 ا إلى مع 􀊻􀊱 د ا رس 􀊗 ف􀊙 ه لة. 􀊽􀊶􀊺 ال 􀇼 اف 􀥽 ض􀊨 ب 􀊙􀊺􀊴 العالي، في جامعة م 􀊦􀥽 عل 􀊱 اع ال 􀊢 ق اره 􀥼􀊱 اع 􀇼 صفي 􀊨 هج ال 􀊻􀊺 اد على ال 􀊺􀊱 الاع 􀊦 قي، وت 􀥽􀊰􀊢 ت 􀊖 وجان 􀈑􀊛􀊤 ن 􀊖 ا رسة على جان 􀊙 ه ال 􀊚 ه 􀊗 ل􀊺􀊱 اش ا رسات . 􀊙 ل هاته ال 􀊲􀊺 ا ل 􀊺 ملائ انة 􀥼􀊱 ع اس 􀈄 ز􀊨􀊱 مات ب 􀊨 عل 􀊺 ع ال 􀊺 ج 􀊦 ا رسة، ت 􀊙 ال 􀊧 ف م 􀊙 ل إلى اله 􀊨 ص􀊨 ات، ولل 􀥽 ض􀊛 ة الف 􀊴 ار ص 􀥼􀊱 ولاخ ل 􀊽 ل􀊴 ة وت 􀥽 ائ 􀊸 ة الاح 􀊳 عال 􀊺 ام أدوات ال 􀊙􀊵􀊱 اس 􀊦 ت 􀊙 ، وق 􀊘􀊴􀥼 ع ال 􀊺􀊱􀊳 م 􀊧 دة م 􀊛 رة ب 68 مف 􀊙 ة مق 􀊻􀊽 على ع 􀊧􀊽 ة ب 􀥽 ائ 􀊸 ة ذات دلالة اح 􀥽 اب 􀊳􀇽 ة إ 􀥽􀊡 ا􀥼 د علاقة ارت 􀊨 ا رسة إلى وج 􀊙 ال 􀊗􀊸 ، وخل 􀊧 اي 􀥼􀊱 وال 􀈌􀥽􀊶􀥼 ار ال 􀊙􀊴 الان العالي . 􀊦􀥽 عل 􀊱 اع ال 􀊢 ة ق 􀊺􀘗􀊨 ح 􀈏 اد 􀥼 ة وم 􀥽􀊺􀥽􀊤􀊻􀊱 قافة ال 􀊲 ال العالي . 􀊦􀥽 عل 􀊱 ة ال 􀊺􀘗􀊨 ة، ح 􀊺􀘗􀊨􀊴 ة، ال 􀥽􀊺􀥽􀊤􀊻􀊱 قافة ال 􀊲 ة: ال 􀥻 اح 􀊯 ف􀊸 ات ال 􀊸 ل􀘒 ال Abstract The actual thesis aims at knowing the role of organizational culture,as an independent variable, in the consecration of the higher education governance principles at Mohamed Boudiaf University of M’sila. This study covers both the theocratical and practical side, by following the descriptive approach which is seen as the most suitable one for these types of studies. To examine the validity of the hypotheses and reach the study’s objectives, data was collected by distributing a questionnaire to a sample of 68. Thus, the statistical tools, simple regression and variance analysis were used. The study’s results concluded that there is a statistically significant correlation between organizational culture and governance principles. Keywords: organizational culture, higher education governance.
Keywords: organizational culture; higher education governance